BASIC ASPECTS OF COMPOSITES BASED ON EPOXY RESIN OR UNSATURATED POLYESTER REINFORCED WITH FIBERS DERIVED FROM ANCHORAGE CABLES - Gonçalves, Ana Carolina Silva; Tamiasso-Martinhon, Priscila; da Silva, Antonio Henrique Monteiro da Fonseca Thomé; da Silva, Célia Regina Sousa; Rocha, Angela Sanches (Editora Impacto Científico, 2025)
The reuse of waste materials for the creation of new products is fully aligned with sustainability principles and is supported by two essential premises: reducing the volume of potentially polluting waste in disposal areas and decreasing the reliance on virgin raw materials. In this context, waste containing synthetic polymers emerges as a particularly relevant candidate for repurposing, given its high potential for environmental impact when improperly discarded. Among these materials, synthetic cables—widely used in the anchoring of floating units—represent, at the end of their service life, a strategic source of high-performance fibers. When reintegrated into production processes, these fibers can act as reinforcement in thermoset-based composites, improving properties such as mechanical strength, thermal stability, and durability in harsh environments. Accordingly, this text presents the fundamentals related to the development of composites based on epoxy and unsaturated polyester resins reinforced with synthetic polyester fibers derived from post-industrial anchoring cables, which may have advanced applications in sectors such as naval structures, automotive components, structural panels, and protection systems. DOI: https://doi.org/10.56238/edimpacto2025.086-002